IMPLEMENTASI DASHBOARD BUSINESS INTELLIGENCE UNTUK VISUALISASI DATA DONATUR (STUDI KASUS: HUMAN INITIATIVE RIAU) - Uun Patrio; Dini Nurmalasari (ABEC Indonesia, 2021)
Human Initiative Riau is one of the humanitarian institutions located in Pekanbaru City which focuses on four areas of work, namely economy, health, education and emergency response. Based on interviews with the Human Initiative, information was obtained that there were several obstacles faced in supporting the activities and programs that were being carried out. The data currently held is still managed conventionally by each division head so that the human initiative is constrained to ascertain whether the program is being implemented according to the target or not. Therefore, a solution is needed that can be used by human initiatives to see the development of donors, donors, beneficiaries and marketers which will later be used as material for evaluating marketer performance and determining future strategies that can improve the performance of human initiatives. This system was built by implementing business intelligence technology with visualization in the form of column-charts and graphs. designed using the codeigniter framework, the programming language PHP and MySQL as its DBMS. This system is tested using testing data transformations, user acceptance test (UAT) and efficiency so that users can find out what improvements they want. Based on the user acceptance test (UAT) that has been carried out, it shows that 96,76% of the systems that have been built are acceptable to users and can help human initiatives in making decisions.